Relationship Between Maternal Age And History Of Abortion With The Incidence Of Abortion At Sawerigading Regional Hospital In 2023 - Jumianti; Irmayanti A Oka; Sridevi Syamsuddin; Hadijah (Jurnal Life Birth, 2023)
Abortion is the expulsion of the products of conception before the fetus can live outside the womb. The risk of spontaneous abortion will increase supported by many parities, the age of the mother, and the spacing of pregnancies that are too close. One of the causes of high rates of spontaneous abortion is anemia caused by impaired nutrition and oxygen circulation to the utero-placental circulation so that it can directly affect the growth of the fetus in the womb through the placenta. The purpose of this study was to determine the relationship between maternal age and history of abortion with the incidence of abortion at Sawerigading Palopo Hospital in 2023. This type of research used a cross-sectional approach. The total population is 33 mothers with the same sample size as the population and using total sampling technique. Data analysis using Chi-square test.there is a relationship between the history of abortion and the incidence of abortion with value(p=0.014 < 0.05). The conclusion of this study is that there is a relationship between maternal age and history of abortion with the incidence of abortion at Sawerigading Palopo Hospital. Suggestions for health agencies are the need to develop counseling programs and increase prenatal monitoring of pregnant women.